OPTIMIZATION OF MODES OF DISSOLUTION OF THE COMPOSITIONS ON HUMPS - Bobrovskyi, V. I.; Kudriashov, A. V. (Science and Transport Progress, 2010)
A method of solving the optimization problem for the mode of breaking up a train, allowing to take into account multiple divisions of its cuts, is developed.